2015
DOI: 10.1039/c5ra01739d
|View full text |Cite
|
Sign up to set email alerts
|

Reactive-template fabrication of porous NiO nanowires for electrocatalytic O2evolution reaction

Abstract: Macro–mesoporous NiO nanowire was demonstrated as an active electrocatalyst for O2 evolution reaction in alkaline media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…It is shown that the multiple-split peaks of Ni 2p 3/2 are located at 854.2 and 856.4 eV and a satellite peak is located at 860.9 eV for Ni 2+ . 31 The multiple-split peaks of Ni 2p 1/2 (872.1 and 874.9 eV) and the Ni 2p 1/2 satellite peak (879.3 eV) are also observable, which is in good agreement with the characteristic peaks of Ni 2+ . When the deposition temperature rises to 800 °C, the two peaks of binding energy at 852.8 and 870.0 eV with a spin energy separation of 17.2 eV confirm the presence of Ni 0 in the samples.…”
Section: Resultssupporting
confidence: 68%
“…It is shown that the multiple-split peaks of Ni 2p 3/2 are located at 854.2 and 856.4 eV and a satellite peak is located at 860.9 eV for Ni 2+ . 31 The multiple-split peaks of Ni 2p 1/2 (872.1 and 874.9 eV) and the Ni 2p 1/2 satellite peak (879.3 eV) are also observable, which is in good agreement with the characteristic peaks of Ni 2+ . When the deposition temperature rises to 800 °C, the two peaks of binding energy at 852.8 and 870.0 eV with a spin energy separation of 17.2 eV confirm the presence of Ni 0 in the samples.…”
Section: Resultssupporting
confidence: 68%
“…24 Thanks to the unique size dependent properties, mass diffusion, and high surface area, nanostructured NiO is oen used as a high-performance OER catalyst. [21][22][23]25,[27][28][29] Finally, graphene supported NiO nanostructures have been demonstrated in the literature to be a very good option, since graphene enhances electron transport and hence catalytic performance, 30 promotes nanostructure dispersion and inhibits their aggregation.…”
Section: Sustainablementioning
confidence: 99%
“…18,19 Among these, Ni oxide represents a promising candidate as an anode material with enhanced electrochemical performances. [20][21][22][23][24][25] Both experimental and theoretical studies suggested that Ni 2+ has more efficient interactions with OH À for the OER compared with other metal (Fe, Mn, Co) oxides which is ideal for catalysts…”
Section: Introductionmentioning
confidence: 99%
“…The low cost, stable, and adequately active transition metal oxides [6,7], hydroxides [8], sulfides [9], nitrides [10], layered double hydroxides [11,12] and perovskites [13,14] have been developed as alternative electrocatalysts. Among them, metal oxides such as MnO 2 [15,16], NiO [17,18], Co 3 O 4 [7,19], and Fe 2 O 3 [20,21] are widely studied due to their wide range of properties such as diverse crystal structures, variable morphologies, and rich redox chemistry governed by coordination environments.…”
Section: Introductionmentioning
confidence: 99%